From Margins to Pluriversality: Refusal, Reconstruction, and Decolonial Futures - Goodell Ugalde, Elliot (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2024)
This document examines the interplay between Audra Simpson's “politics of refusal” and Subcomandante Marcos' “pluriversalism”—both emerging from postcolonial discourse on Turtle Island—as frameworks aiming for self-determined governance that authentically acknowledges Indigenous knowledge(s) and ways of being. Simpson advocates for an emancipatory refusal to accept settler-state recognition, which often marginalises Indigenous perspectives and relegates them to a “peripheral” or “deviant” status within educational institutions and policies. In contrast, Marcos' pluriversalism, while also challenging the state's homogenising force, promotes a dialogical engagement that incorporates Mesoamerican knowledge(s) to enrich mainstream discourses, fostering “border thinking” or “border epistemology.”This analysis proposes that Simpson's approach effectively deconstructs prevailing hierarchical knowledge structures within education, while Marcos' method seeks to reconstruct more inclusive paradigms where diverse epistemologies coexist without perpetuating colonial dominance. Thus, the thesis advocates for a two-step decolonial process with significant implications for educational practice, policy, and pedagogy: (1) Implementing Simpson's politics of refusal to critically dismantle the dominance of colonial epistemologies in curricula, teaching methods, and educational policies, effectively breaking down hierarchical relationships between colonial and Indigenous knowledge systems; and (2) Employing Marcos' pluriversal approach to reconstruct educational paradigms, fostering policies and pedagogical practices that support the equitable coexistence of different, and often competing, epistemologies and ontologies. This dual strategy aims to transform educational systems, preventing the perpetuation of colonial imbalances and promoting a truly inclusive, pluriversal educational landscape.